Analisis Kelengkapan Peralatan Praktek Dasar Listrik Elektronika di SMK - Agung Satria; Muldi Yuhendri (Jurnal Pendidikan Teknik Elektro, 2021)
Education is a systematic process to increase the dignity of human development in a holistic manner, which enables the full potential of individuals so that the aspirations of developing Indonesian people as a whole can be achieved. Completeness of equipment or facilities is the level of achievement in the form of the number of facilities that are directly used for practical learning by Electrical Installation and Power Engineering students with the standard number that should be owned by the school or department. This research is a descriptive study which aims to analyze the completeness of workshop practice equipment using quantitative descriptive method. The research was conducted with data starting from several methods (observation, portfolio, questionnaire, and documentation) which were then adjusted to the research instruments that had been prepared. The results of the research conducted show that the completeness of practical equipment at Muhammadiyah 1 Padang Vocational School with student learning outcomes in Basic Electrical and Electronics subjects is proven by 25 students categorized as complete, and proposing 10 approximate aspects, then the appropriate answer is found, the number of students who complete more number of students who did not complete.